"Cloister in a Carnival": Electric Light and Gendered Atmospheres in F. Scott Fitzgerald's Manhattan. Issue 1 (2nd January 2018) - Walls, Adam
Abstract : This essay investigates the "political aesthetics" of electric lighting in Manhattan during 1913–1922, particularly the conflicting styles of public and private lighting, both urban and domestic, portrayed within F. Scott Fitzgerald's 1922 The Beautiful and Damned . Using the method of "topographic literary analysis", it traces the novel's two main protagonists, of different gender and class, as they move through New York and its various levels of society. At times, Fitzgerald's own perspective is introduced via other autobiographical writings. Two main points are emphasised: firstly, "topographic" literary analyses might provide an embodied-relational method for re-narrating and accurately situating historical experience, particularly its subtler, affective, or atmospheric properties previously deemed too difficult to register by historians; secondly, electric lighting is shown to hold significant agency over Fitzgerald's human protagonists, acting not as a mere prop, but a third protagonist in and of itself, with effects that are both highly gendered and classed.